Intrinsic Element Analysis of Novel: The Forbidden Heaven by Leyla Hana: Analisis Unsur Intrinsik Novel: Surga Terlarang oleh Leyla Hana - Safitri Said; Ibnu Rawandhy N. Hula (Lembaga Pengembangan Kinerja Dosen, 2022)
This study analyzes the intrinsic elements of a novel that is widely read by the Indonesian people because it contains Teenlit and Chicklit simultaneously. This research uses a type of literature study research. Data collection was carried out by the method of documentation from primary sources in the form of a novel entitled